Creation and content validity of a scale for assessing adherence to good practices for COVID-19 - Meneguin, Silmara [UNESP]; Pollo, Camila Fernandes [UNESP]; Garuzi, Miriane [UNESP]; Morais, José Fausto de; Reche, Mariana Cristina [UNESP]; Melchiades, Ediana Preisler [UNESP]; Coró, Cintia [UNESP]; Segalla, Amanda Vitória Zorzi [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: to create a scale for assessing the adherence of healthcare providers to good practices for COVID-19 in the hospital setting and determine its content and face validity. METHODS: A methodological study was developed in three sequential phases: creation of items and domains based on a literature review and administration of the questionnaire to 16 nursing professionals; assessment of content and face validity by experts; and semantic analysis. RESULTS: The 51-item scale was submitted to the evaluation of seven experts. Items with a content validity index ≥ 0.83 were maintained. During the semantic analysis performed by the administration of the scale to 37 healthcare providers, no suggestions for changes were made and the comprehension rate was 87%. CONCLUSIONS: the 47-item instrument with three dimensions (personal, organizational, and psychosocial) achieved satisfactory content and face validity, meeting the parameters established in the literature.